2017
DOI: 10.1111/inm.12325
|View full text |Cite
|
Sign up to set email alerts
|

Lethal hopelessness: Understanding and responding to asylum seeker distress and mental deterioration

Abstract: The mental deterioration of the so called ‘legacy caseload’ (asylum seekers who arrived in Australia by boat between August 2012–December 2013) has become a national concern and is garnering international attention. Prolonged uncertainty is contributing to mental deterioration and despair. There have been at least 11 deaths by suicide since June 2014. Social support services have been limited and legal assistance in short supply; this is associated with lengthy delays with visa applications. Thwarted belonging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 27 publications
(44 reference statements)
2
40
0
Order By: Relevance
“…Notably, this finding was robust even after controlling for key factors that are known to contribute to mental health in refugees, including gender, education, time in Australia, and PTE exposure. The association between visa insecurity and suicidality is especially notable, with Procter, Kenny, Eaton, and Grech (2018) coining the term 'lethal hopelessness' to describe this phenomenon. They posit that lengthy delays in processing of asylum or other visa-related applications, combined with limitations on access to mainstream services, financial support and work rights, lead to mental deterioration amongst people seeking asylum, which has resulted in a spate of successful suicide attempts in Australia in recent years (Barry, 2018;Observatory, 2018;Doherty, 2017Doherty, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this finding was robust even after controlling for key factors that are known to contribute to mental health in refugees, including gender, education, time in Australia, and PTE exposure. The association between visa insecurity and suicidality is especially notable, with Procter, Kenny, Eaton, and Grech (2018) coining the term 'lethal hopelessness' to describe this phenomenon. They posit that lengthy delays in processing of asylum or other visa-related applications, combined with limitations on access to mainstream services, financial support and work rights, lead to mental deterioration amongst people seeking asylum, which has resulted in a spate of successful suicide attempts in Australia in recent years (Barry, 2018;Observatory, 2018;Doherty, 2017Doherty, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Robinson () found that immigration policy in Australia and the United Kingdom placed additional stress on social workers working with refugees and asylum seekers. Many authors have written about Australia's immigration policy being one which promotes deterrence, detention, and destitution (Gammeltoft‐Hansen, ; Kenny, Procter, & Grech, ; Procter et al, ; Silove et al, , ) and Robinson () found that, in turn, these policies created challenges for the workers in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Less research has considered the effects, positive or negative, of working with individuals from refugee and asylum seeker backgrounds who have experienced torture and trauma. Clinicians who work with refugees and asylum seekers are also exposed to traumatic narratives, but this is in addition to numerous other challenges such as working within the context of immigration detention, refugee status determination, visa applications and rejections, uncertainty for the clients' futures, and a multitude of social and resettlement challenges (Akinsulure-Smith & O'Hara, 2012;Apostolidou, 2016;Procter, Kenny, Eaton, & Grech, 2018). The adverse mental health impacts of immigration detention and prolonged refugee status determination for asylum seekers are well documented (Robjant, Robbins, & Senior, 2009;Silove, Steel, & Watters, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the associations between mental illness and war trauma have been well documented [1], the recent Mediterranean crisis [2] has not received attention from policymakers, especially in terms of suicide prevention. Research indicates that post-traumatic stress disorder (PTSD) and depression are prevalent among refugees, whilst the challenging environment in detention centres and the prolonged asylum-application process seem to affect mentalhealth well-being further [3][4][5].…”
mentioning
confidence: 99%